Effect of deuterium implantation dose on properties of CrN coatings - Kuprin, A.S.; Belous, V.A.; Morozov, O.M.; Ovcharenko, V.D.; Dub, S.N.; Tolmachova, G.N.; Reshetnyak, E.N.; Zhurba, V.I.; Progolaieva, V.O. (Вопросы атомной науки и техники, 2017)
The methods of X-ray diffraction analysis, atomic-force microscopy, nanoindentation and thermodesorption spectroscopy have been applied to investigate the effect of a dose (from 5∙10¹⁶ to 1.5∙10¹⁸ D/сm²) of implanted deuterium with energy of 24 keV on the structure, surface morphology and mechanical properties of vacuum-arc CrN coatings. Deuterium ion implantation in the range of doses from 5∙10¹⁶ to 1.5∙10¹⁷ D/сm² decreases by 10…15% the nanohardness and elastic modulus of coatings. Under exposition to doses ≥ 1∙10¹⁸ D/сm² the coating nanohardness sharply decreases because of blisters being formed and occupying about 30% of the CrN coating surface. Deuterium implantation did not lead to formation of new phases in the CrN coating. Методами рентгеноструктурного аналізу, атомно-силової мікроскопії, наноіндентування і термодесорбційної спектроскопії досліджено вплив дози (5∙10¹⁶…1.5∙10¹⁸ D/см²) імплантованого дейтерію з енергією 24 кеВ на структуру, морфологію поверхні та механічні властивості вакуумно-дугових покриттів CrN. Імплантований дейтерій в інтервалі доз 5∙10¹⁶…1.5∙10¹⁷ D/см² призводить до зменшення на 10…15% нанотвердості і модуля пружності покриттів. Опромінення дозами ≥ 1∙10¹⁸ D/см² викликає різке зниження нанотвердості покриттів через формування блістерів, які займають близько 30% поверхні покриття CrN. Імплантація дейтерію не призводить до утворення нових фаз у покритті CrN. Методами рентгеноструктурного анализа, атомно-силовой микроскопии, наноиндентирования и термодесорбционной спектроскопии исследовано влияния дозы (5∙10¹⁶…1,5∙10¹⁸ D/см²) имплантированного дейтерия с энергией 24 кэВ на структуру, морфологию поверхности и механические свойства вакуумно-дуговых покрытий CrN. Имплантированный дейтерий в интервале доз 5∙10¹⁶…5∙10¹⁷ D/см² приводит к уменьшению на 10…15% нанотвердости и модуля упругости покрытий. Облучение дозами ≥ 1∙10¹⁸ D/см² вызывает резкое снижение нанотвердости покрытий из-за формирования блистеров, которые занимают около 30% поверхности покрытия CrN. Имплантация дейтерия не приводит к образованию новых фаз в покрытии CrN.